Inovasi Siswa SMA/SMK untuk Memecahkan Isu Pangan, Energi dan Lingkungan di Provinsi Sumatera Selatan - Oktaf Juairiyah; Dian Novriadhy; Hendrixon Hatta (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Juairiyah O, Novriadhy D, Hatta H. 2020. High school/vocational high school students innovation to solve issues of food, energy and the environment in South Sumatra province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The availability of food, energy, and the sustainability of environmental carrying capacity is three global problems that need to be resolved immediately in an innovative way. This study aims to explain the proportion of SMA/SMK students' innovations to solve problems in food, energy, and environmental sustainability. Data sourced from proposals for high school/vocational high school level innovation competitions organized by South Sumatra's Provincial Government. This research is cross-sectional with a quantitative descriptive approach. The research variables consisted of the type of innovation, the innovation sector, and the kind of school. The collected data is processed and interpreted through the statistical concept of different tests. The results showed that as much as 72.3% of innovations came from high school students in 6 innovation sectors with the most popular food sector and tend to be applied so that infrastructure support needs technology readiness, development incentives, and outwall incubators that these innovations are implement in society.